2005
DOI: 10.4028/www.scientific.net/ssp.108-109.261
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Carbon Related Defects in Low-Temperature Irradiated Si: FTIR and DLTS Studies

Abstract: The evolution of radiation-induced carbon-related defects in low temperature irradiated oxygen containing silicon has been studied by means of Fourier transform infrared absorption spectroscopy (FTIR) and deep level transient spectroscopy (DLTS). FTIR measurements have shown that annealing of interstitial carbon atom Ci, occurring in the temperature interval 260-300 K, results in a gradual appearance of a number of new absorption bands along with the well known bands related to the CiOi complex. The new bands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Figure a displays the DLTS spectra for set A sample, and the dominant peak in the as‐irradiated diode is a characteristic signature of the well‐known C i O i complex and appears to consist of two overlapping peaks. It has been reported previously that after irradiation at RT a precursor state, C i O i *, appears and persists up to 50 °C before the transition to the stable C i O i state …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Figure a displays the DLTS spectra for set A sample, and the dominant peak in the as‐irradiated diode is a characteristic signature of the well‐known C i O i complex and appears to consist of two overlapping peaks. It has been reported previously that after irradiation at RT a precursor state, C i O i *, appears and persists up to 50 °C before the transition to the stable C i O i state …”
Section: Resultsmentioning
confidence: 89%
“…The evolution of C i O i upon post‐irradiation thermal treatments has been studied intensively for decades. In previous deep level transient spectroscopy (DLTS) studies, metastable configurations of C i O i has been reported during isochronal annealing of irradiated Si in the temperature range 280–360 K. It has been suggested that an intermediate state, referred to as C i O i *, appears before the formation of a stable C i O i that persists up to 400 °C. Annealing of C i O i has also been studied by photoluminescence spectroscopy (PL) via monitoring the so‐called C‐line at 789 meV .…”
Section: Introductionmentioning
confidence: 99%
“…4). Comparing with literature data, 14,15,[25][26][27][28][29][30] it is concluded that the hole trap found in the p-type silicon substrate after RTA most likely corresponds with C i O i -related centers, although the σ p is about one decade higher than the typically reported values. This could be due to the effect of the negative feature observed in Fig.…”
Section: Discussionmentioning
confidence: 46%
“…In fact, comparing with the data of Ref. 30, one can conclude that the experimental points in Fig. 10 are closer to the Arrhenius plot for the C i O i * precursor center than to the C i O i data.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation